Influence of Sales Promotion and Service Quality on Consumer Purchasing Interest in Grab's Online Transportation Services: A Case Study among Students at Universitas Negeri Medan - Aswin Bancin*; Astri Novia Siregar (Universitas Syiah Kuala, 2023)
Abstract: This study aims to conduct a thorough investigation and analysis of the profound impact of two primary factors on consumer purchase intention in adopting the Grab online transportation service. The research took place within the premises of Universitas Negeri Medan and involved 169 students as the primary subjects. Data collection employed a questionnaire with a five-point scale to uncover consumer perceptions and preferences. The sampling technique utilized was proportional random sampling, ensuring the sample represented the population variations among students. Before widespread use, the questionnaire instrument underwent pilot testing on respondents outside the sample to measure its validity and reliability, ensuring the precision and dependability of the measurement tool. Instrument validity was assessed through the Product Moment correlation method, while reliability was tested via the calculation of Cronbach's Alpha coefficient. Preceding hypothesis testing, several prerequisite analyses were conducted, including data normality testing to ensure the data used in analysis adhered to appropriate distribution, and regression linearity testing to examine the linearity of relationships between variables. The findings of the study indicate that, firstly, sales promotion strategies have a significant positive impact on consumer purchase intention towards the Grab online transportation service. Secondly, service quality also possesses a robust positive influence on consumer purchase intention. By endorsing the proposed hypotheses, this research successfully formulated a robust theoretical model, delineating the framework of causal relationships between sales promotion, service quality, and consumer purchase intention in the context of utilizing the Grab online transportation service within the Universitas Negeri Medan environment. These findings offer valuable insights into the factors shaping consumer preferences and behaviors in selecting online transportation services